Techno-feasibility assessment on utilization of rice husk and wood scrap as energy sources of the rotary drier while drying BSF maggot - Purwaka, Purwaka; Susastriawan, Anak Agung Putu; Saputra, Hadi; Rahayu, Suparni Setyowati; Hidayat, Taufiq; Sidharta, Bambang Wahyu; Mathur, Akanksha (Journal of Engineering and Applied Technology, 2024)
Black Soldier Flies (BSF) maggot business got increasing attention nowadays, especially dried BSF maggot. The dried BSF maggot is very suitable for fish feed, thus dried maggot business has good prospectus not only in terms of financial sector but also in terms of waste management sector. Unfortunately, making dried maggot requires high cost during drying process, since additional cost for LPG is needed. It is important to replace LPG fuel by less expensive one, such as biomass fuel. Indonesia has huge potential of biomass energy sources which mainly come from agricultural, forestry, and industrial waste. The present work aims to investigate techno-feasibility of rice husk and waste scrap waste as feedstock of rotary drum drier. The experimental work is conducted by drying 10 kg fresh BSF maggot for 2 hours in the drier using blend feedstock of 6 kg rice husk- 6 kg wood scrap (RH-WS) and feedstock of 12 kg wood scrap (WS). The results depict that the waste of rice husk and wood scrap are technological feasible as energy sources for rotary drum dryer while drying BSF maggot. The performance of the drier in terms of drying rate, drying heat, specific fuel consumption, and drier's effectiveness is better when a blend of rice husk and wood scrap is used as a feedstock. The values of drying rate, drying heat, specific fuel consumption, and drier's effectiveness when using blend feedstock are 0.92 g/s, 20996.37 kJ, 27940.15 kJ/kg, and 0.67, respectively. It is recommended to use waste of rice husk and wood scarp in blending form to obtain optimum performance of the rotary drier while drying BSF maggot.